Ground vibration induced by moving vehicle on soft soil - Engku Ab Rahman, Engku Shahrulerizal; Zainorabidin, Adnan; Mahfidz, Hazlina; Mohamad, Habib Musa (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
This research was conducted to gain more knowledge and investigate the ground vibration induced by vehicle at five different bridge approach location in Batu Pahat, Johor. This research also to illustrate and specify the ground vibration value based on identifying the location of an influence class of vehicle, speed of vehicle and zone of vehicle on bridge approach which are passing through to the bridge approach A (BAA) and bridge approach B (BAB). In describing vibration in the ground and in structures, the motion of the particle is utilized. This research describes the concepts of particle displacement, velocity and acceleration that are used to depict how the ground or structure reacts to excitation. This research observed the ground vibration motion, that is commonly described by identifying the peak particle velocity (PPV). Also presented, a description of the measurement technique, procedures and field data collection. From the sight of view of the result of this research, it indicated that the vibration value is more significant by all the variables. As a result, by the comparison of the variables that had been conducted with respect to the value of this vibration, it was found that the zone near the sensor shows a higher PPV value compared to the zone that is far apart from the sensor location and also vehicle class also plays a role which class IV is higher than class III and class II. The research shows potential to provide and improve the knowledge towards the importance of ground vibration from the vehicle loading by specific evaluation.